The Influence of Health Promotion through Leaflet Media on Students Knowledge about Handwashing with Soap - Azizi, Shita Ayu; Salianto, Salianto; Astuty, Delfriana Ayu (Indonesian Journal of Global Health Research, 2024)
Handwashing with soap is crucial in preventing infectious diseases, especially in school environments. However, students' knowledge about this is often suboptimal. Health promotion through leaflet media can be an effective solution to improve students' knowledge about handwashing with soap. The aim of this study is to determine the effect of health promotion through leaflet media on students' knowledge of handwashing with soap at SDN 105361 Lubuk Cemara, Perbaungan District. This research uses quantitative research, a quasi-experimental design with a one-group pre-test-post-test approach. The research sample consisted of 70 fifth-grade students selected through purposive sampling. The data collection method used in the study is a questionnaire on handwashing with soap. Data analysis conducted includes univariate analysis and bivariate using the non-parameteric Wilcoxon test. The results of the Wilcoxon statistical test obtained a pvalue = 0.000 (p < 0,05) with an average increase in pretest and post-test knowledge of 4.88. There is an influence of health promotion through leaflet media on students' knowledge levels regarding handwashing with soap at SDN 105361 Lubuk Cemara, Perbaungan District.